Presto-Color: A Photometric Survey Cadence for Explosive Physics and Fast Transients. (25th April 2019) - Bianco, Federica B.; Drout, Maria R.; Graham, Melissa L.; Pritchard, Tyler A.; Biswas, Rahul; Narayan, Gautham; Andreoni, Igor; Cowperthwaite, Philip S.; Ribeiro, Tiago
Abstract: We identify minimal observing cadence requirements that enable photometric astronomical surveys to detect and recognize fast and explosive transients and fast transient features. Observations in two different filters within a short time window (e.g., g -and- i, or r -and- z, within <0.5 hr) and a repeat of one of those filters with a longer time window (e.g., >1.5 hr) are desirable for this purpose. Such an observing strategy delivers both the color and light curve evolution of transients on the same night. This allows the identification and initial characterization of fast transient—or fast features of longer timescale transients—such as rapidly declining supernovae, kilonovae, and the signatures of SN ejecta interacting with binary companion stars or circumstellar material. Some of these extragalactic transients are intrinsically rare and generally all hard to find, thus upcoming surveys like the Large Synoptic Survey Telescope (LSST) could dramatically improve our understanding of their origin and properties. We colloquially refer to such a strategy implementation for the LSST as the Presto-Color strategy (rapid-color). This cadence's minimal requirements allow for overall optimization of a survey for other science goals.